Estudio de viabilidad social para la implementación de huertas urbanas con un sistema de riego ecológico y autónomo en la ciudad de Bogotá DC. (2022)
Currently, based on the increase in trends in the consumption of organic products, which allow a healthier lifestyle, the idea of ​​implementing urban gardens is obtained. In this sense, the purpose of this document is to prepare the social feasibility study for the implementation of urban gardens with an ecological and autonomous irrigation system in the city of Bogotá DC, through the search for conceptual, theoretical and practical information regarding the study topic that allows an approach to it, providing a clear vision and a starting point for the development of the research proposal.